PARAMETRIC STUDY OF A SOLAR DRYER SYSTEM FOR THE DEVELOPMENT AND APPLICATION OF SOLAR ENERGY IN SIERRA LEONE - Bangura, Abu Bakarr Momodu; Hantoro, Ridho; Fudholi, Ahmad; Uwitije, Pierre Damien (Journal of Applied Engineering Science, 2022)
A transient mathematical model has been evaluated to determine the principle of a solar crop dryer for drying vegetables (onion).  Considering the meteorological conditions of Freetown (Latitude 8.4840 N, Longitude -13.2300 W), the model was developed to determine air temperatures and other operational parameters of the drying system for a day of March 21st. However, the investigated system had effectively reduced the drying process of onion. The developed double-pass solar air collector system showed a low-temperature output in the morning hours and displayed high-temperature results in the afternoon hours. From 8:00 to 16:00, the solar collector generates fluid output temperatures above 50 0C, with a peak value of 96 0C occurred at 12:00. The influence of the mass flow rate on the system's thermal efficiency was investigated. It was noticed that for a certain solar radiation value, an increased in the mass flow rate caused an exponential increased in the solar air collector thermal efficiency. Findings also revealed that an increased in the solar collector length led to a slightly decreased in the outlet air temperatures at a mass flow rate of 0.02 kg/s. The influence of increasing drying air temperatures and air velocity within the drying chamber reduces drying time significantly. The drying time for products dried in the first tray is lesser than for products dried in the subsequent trays, owing to temperature variations. The computation findings were verified to previous studies in the literature and observed to be strongly comparable.
Keywords: double-pass collector, drying chamber, mathematical model, onion, solar energy in Sierra Leone, thermal efficiency